WEST POMERANIAN HEALTH TOURISM ON THE BACKGROUND OF SOCIO-ECONOMIC TRANSFORMATIONS OF THE EUROPEAN UNION - Bogusław Stankiewicz (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article addresses the attempt of a new reading of the growth prospects for the health tourism sector in the region through the confronting phenomena and processes which objectively affect the present and future socio-economic growth trends in the European Union in the face of institutional arrangements. Analysing the conditions in the external environment of the sector – macro and meso levels – the existence of two trends was proved: 1) mismatch (fossilization) between national tourism development strategies (health tourism sector) to qualitative changes in the European Union (megafactors of development) during 2) the attempt to give a new impetus of development to health tourism through the incorporation into the framework of broader institutional arrangements which can be observed in the German federal lands neighbouring with West Pomerania., that is, regional sector development policy as a component within the booming health economy.